Synthesis and Structure of a New Pentanary One-Dimensional Palladium Thiophosphate, K2PdPS4I - Yoon, Woojin; Yun, Hoseop (Bulletin of the Korean Chemical Society, 2021)
The new pentanary thiophosphate, K2PdPS4I was prepared with the use of the reactive halide flux and the crystal structure of the compound was determined by single-crystal X-ray diffraction method. The structure of K2PdPS4I is comprised of anionic infinite one-dimensional (Formula presented.) [PdPS4−] chains separated from one another by the K+ ions. In addition, The K+ ions surround the I− ions through ionic interactions, but there is no direct contact between I− and S2− ions. Although the title compound, K2PdPS4I can be regarded as a combination of KPdPS4 and KI, the one-dimensional (Formula presented.) [PdPS4−] chain found in the title compound is different from that of the previously reported KPdPS4. The bond valence calculations and the structural features indicate that the charge balance of the title compound should be described as [K+]2[Pd2+][P5+][S2−]4[I−].
Keywords: Bond valences; Charge balances; Direct contact; Ionic interaction; Pentanary; Single crystal X-ray diffraction method; Structural feature; Title compounds; Crystal structure; One-dimensional chain; Thiophosphate